Starhub : re-inventing a traditional pay-TV model - Loon, Melissa Shu Juan (Nanyang Technological University, 2013)
The case explores the impact of breakthrough technology advancements and evolving consumer trends on StarHub’s pay-TV business unit. Strong relationships with content owners and well-suited consumer offerings were key to StarHub pay-TV’s success. Yet, a change in the underlying concept of entertainment has altered the relationships between StarHub and its key stakeholders. The case explores how StarHub can re-align its pay-TV business to tap on new critical success factors in the future.